1976
DOI: 10.1136/bmj.2.6050.1473
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal calcium metabolism in normocalcaemic sarcoidosis.

Abstract: SummaryIn studies of calcium metabolism in 13 unselected patients with untreated sarcoidosis all were normocalcaemic but five had hypercalcuria. All had normal renal function. Calcium absorption was indexed by a double isotope test. 45Ca hyperabsorption occurred in six patients. Ten kinetic studies were carried out with 47Ca and in six bone turnover was increased. 45Ca absorption correlated well with the calculated bone uptake rate of calcium, and with urine calcium excretion.These results suggest that in sarc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1979
1979
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…Abnormal calcium metabolism in sarcoidosis is characterized by enhanced intestinal absorption of the ion and hypercalciuria with or without hypercalcemia, which may be associated with renal stones, nephrocalcinosis, and impaired renal function (1)(2)(3)(4)(5)(6)(7)(8). Patients with sarcoidosis exhibit increased sensitivity to small doses of vitamin D, which are ineffective in normal subjects (1,(4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
“…Abnormal calcium metabolism in sarcoidosis is characterized by enhanced intestinal absorption of the ion and hypercalciuria with or without hypercalcemia, which may be associated with renal stones, nephrocalcinosis, and impaired renal function (1)(2)(3)(4)(5)(6)(7)(8). Patients with sarcoidosis exhibit increased sensitivity to small doses of vitamin D, which are ineffective in normal subjects (1,(4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
“…They proposed that bone resorption due to cumulative effects of calcitriol on osteoclasts and/or bone granuloma and of an osteoclast-activating factor produced by sarcoid granuloma may also have contributed. Reiner et al, 14 who performed calcium absorption and kinetic studies in 13 normocalcemic patients with untreated sarcoidosis, found evidence of calcium hyperabsorption from the gut and increased bone turnover. PTH did not seem to be responsible for increased bone turnover.…”
Section: Discussionmentioning
confidence: 97%
“…From low phosphate excretion index values in their patients, they inferred a reduced biological effect of PTH. 14 Physiologic requirements for calcium increase during normal pregnancy to meet the needs of growing fetus and to maintain maternal plasma and bone calcium concentrations. 11 Gertner et al 15 described pregnancy as a state of physiologic absorptive hypercalciuria.…”
Section: Discussionmentioning
confidence: 99%
“…The most important protection in preventing the complications of vitamin D intoxication is to monitor serum calcium concentrations and urinary calcium excretion frequently. Hypercalcemia is found in about 17% of all patients with sarcoidosis and associated with increased intestinal absorption of calcium and increased calcium release from bone [22]. The pathogenesis of hypercalcemia in sarcoidosis is extrarenal [23].…”
Section: Metabolic Factorsmentioning
confidence: 99%